Emotional intelligence in educational leadership doctoral students: Measuring the association between gender and age (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This study examined differences between females and males in emotional intelligence (EI). The researchers conducted a test of association between EI and sex and on age in a sample of educational leadership doctoral students. Using a survey, the principal investigator collected measures on EI and other demographic information from the participants. The sample was made up of 36 educational leadership students (24 women and 12 men) attending a regional university located in the southern region of the United States. EI was evaluated by the Schutte Self-Report EI Test (Schutte et al., 1998), which evaluates four subscales (Perception of Emotion, Utilization of Emotion, Managing own Emotions, and Managing Others’ Emotions). When the researchers examined EI as a trait, they were unable to detect differences in EI based on gender and based on age. Additional research is needed to further understand EI in educational leadership doctoral students.